Application of Falling Weight Deflectometer (FWD) and Synthetic Fiber in the Asphalt Mixture: A Review - Ab.Aziz, Siti Hanisah; Mohamad Taher, Mohammad Nasir (Recent Trends in Civil Engineering and Built Environment, 2021)
Fiber Reinforced Asphalt Concrete (FRAC) has been widely used in highway engineering to improve the pavement performance. The addition of synthetic fiber into asphalt mixture could increase the strength of the pavement as it has very high tensile strength. These materials were design to enhance the current mix design pavement as fibers will not melt when mix into asphalt because it has strength and durability to withstand in high and low temperature. The combination of synthetic fiber increases the properties of elastic modulus in the pavement mixture design compared to without combination of synthetic fiber. However, the properties of certain types of fiber decreases when the addition percentage of fiber into the asphalt mixture such as the combination of polyolefin-glass fiber where the resilient modulus reading is decreasing when added 0.18% of polyolefin-glass fiber compared to 0.12% of polyolefin-glass mix in asphalt mixture. Structural pavement evaluations by using Falling Weight Deflectometer (FWD) were used to assess the structural condition of pavement. The data from previous studies which collected applied using FWD were analyzed by the process of backcalculation whereas performed using computer programs. Through the data obtained, this study considered a few parameters which is measured the vertical deflection due to the load applied, the correlation of the elastic modulus of pavement.